Peranan Pendidikan Pemakai Dalam Pemanfaatan Layanan Perpustakaan Di Universitas Muhammadiyah Sumatera Utara - Muhammad Nauval Daffari; Sakti Ritonga; Franindya Purwaningtyas (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study discusses the Role of User Education in the Utilization of Library Services at Muhammadiyah University of North Sumatra, where the core problem described in the research is the impact of the role of user education activities which is the library business of Muhammadiyah University of North Sumatra in educating library users about library facilities and services.The research in this thesis uses a descriptive qualitative method. This study describes and describes the data to obtain analysis according to the research title. The purpose of this study is to determine the role of user education activities on user knowledge in utilizing library services. The informants in this study consisted of library staff, library volunteers and final semester students from the faculties of social sciences and law at Muhammadiyah University, North Sumatra. The results of this study show that user education activities have a specific target which is new students at the Muhammadiyah University of North Sumatra. The role of this user education activity has a good impact and advances student knowledge about using library services and facilities properly. User education activities are also carried out as a tool for socializing between libraries and users, then the prominent role of user education is that the majority of users have properly utilized library facilities such as OPAC, reference services and volunteered to become library volunteers.